Expanding the Benefits of Tnt1 for the Identification of Dominant Mutations in Polyploid Crops: A Single Allelic Mutation in the MsNAC39 Gene Produces Multifoliated Alfalfa - Jozefkowicz, Cintia; Gómez, Cristina; Odorizzi, Ariel; Iantcheva, Anelia; Ratet, Pascal; Ayub, Nicolás; Soto, Gabriela (Frontiers in Plant Science, 2021)
Most major crops are polyploid species and the production of genetically engineered cultivars normally requires the introgression of transgenic or gene-edited traits into elite germplasm. Thus, a main goal of plant research is the search of systems to identify dominant mutations. In this perspective article, we show that the Tnt1 element can be used to identify dominant mutations in allogamous tetraploid cultivated alfalfa. Specifically, we show that a single allelic mutation in the MsNAC39 gene produces multifoliol leaves (mfl) alfalfa plants, a pivot trait of breeding programs of this forage species. Finally, we discuss the potential application of a combination of preliminary screening of beneficial dominant mutants using Tnt1 mutant libraries and genome editing via the CRISPR/Cas9 system to identify target genes and to rapidly improve both autogamous and allogamous polyploid crops.